Awareness, knowledge, attitude and practice of adverse drug reaction reporting among health workers and patients in selected primary healthcare centres in Ibadan, southwestern Nigeria - Rasaq Adisa; Tomilayo I. Omitogun (BMC, 2019)
Abstract Background Higher incidence of adverse drug reactions (ADRs) is a global health problem requiring attention of all stakeholders regardless of the practice settings. This study therefore aimed to evaluate awareness, knowledge, attitude and practice of ADR reporting among health workers and patients in 10 primary healthcare centres (PHCs) in Ibadan, southwestern Nigeria. Methods Questionnaire-guided cross-sectional survey among 80 health workers and 360 patients enrolled from the selected PHCs between October and December 2018. The semi-structured questionnaires generally comprised open-ended and closed-ended questions to explore general knowledge and awareness of ADRs and pharmacovigilance, while other question-items evaluated attitude towards ADR reporting and ADR reporting practice. Overall percent score in the knowledge and attitude domains for the health workers was developed into binary categories of > 80 versus ≤80% for "adequate" and "inadequate" knowledge, as well as "positive" and "negative" attitude, respectively. Data were summarised using descriptive statistics, while Chi-square test was used to evaluate categorical variables at p < 0.05. Results Overall, 58(72.5%) health workers had heard of pharmacovigilance, but only 3(5.2%) correctly understood the pharmacovigilance concept. Twelve (15.0%) showed adequate knowledge of ADRs, while 37(46.2%) demonstrated positive attitude towards ADR reporting. Thirty (37.5%) health workers had come across ADR reporting form, while 79(98.8%) expressed willingness to report all ADRs encountered. Of the patients, 31(8.6%) had heard of pharmacovigilance, 143(39.7%) correctly cited ADR definition, while 67(18.6%) reported the previously experienced ADRs. Informing healthcare professional (38; 38.8%) was the most common measure taken by patients when they experienced reaction(s). Nurses significantly had adequate knowledge of ADRs (p < 0.001) compared to other cadres. Conclusions Health workers in the selected PHCs were largely aware of pharmacovigilance but show low level of knowledge about ADRs and pharmacovigilance concept, with moderately positive attitude towards ADR reporting. Patients on the other hand demonstrate low level of awareness of pharmacovigilance and ADR reporting, with less than one-fifth who reported the previously experienced ADRs. This perhaps underscores a need for regular mandatory education and training on ADRs/pharmacovigilance concept among the PHC health workers, while continuous public enlightenment and awareness campaign on spontaneous reporting of ADRs is advocated in order to enhance reporting rate.